Divergent Processes Drive Parallel Evolution in Marine and Freshwater Fishes. (6th November 2021) - Friedman, S T; Collyer, M L; Price, S A; Wainwright, P C
Abstract: Evolutionary comparisons between major environmental divides, such as between marine and freshwater systems, can reveal the fundamental processes governing diversification dynamics. Although processes may differ due to the different scales of their biogeographic barriers, freshwater and marine environments nevertheless offer similar opportunities for diversification in benthic, demersal, and pelagic habitats. Here, we compare the evolutionary patterns and processes shaping teleost diversity in each of these three habitats and between marine and freshwater systems. Using specimens from the National Museum of Natural History, we developed a data set of linear measurements capturing body shape in 2266 freshwater and 3344 marine teleost species. With a novel comparative approach, we contrast the primary axis of morphological diversification in each habitat with the major axis defined by phylogenetic signal. By comparing angles between these axes, we find that fish in corresponding habitats have more similar primary axes of morphological diversity than would be expected by chance, but that different historical processes underlie these parallel patterns in freshwater and marine environments. Marine diversification is more strongly aligned with phylogenetic signal and shows a trend toward lineages occupying separate regions of morphospace. In contrast, ecological signal appears to be a strong driver of diversification in freshwater lineages through repeated morphological evolution in densely packed regions of morphospace. In spite of these divergent histories, our findings reveal that habitat has driven convergent patterns of evolutionary diversification on a global scale. [Benthic–pelagic axis; body shape; convergent evolution; morphological diversification; phylogenetic signal.]